2002
DOI: 10.1074/jbc.m108808200
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Inhibition of cAMP Signaling

Abstract: Zn2؉ is required as either a catalytic or structural component for a large number of enzymes and thus contributes to a variety of important biological processes. We report here that low micromolar concentrations of Zn 2؉ inhibited hormone-or forskolin-stimulated cAMP production in N18TG2 neuroblastoma cells. Similarly, low concentrations inhibited hormone-and forskolin-stimulated adenylyl cyclase (AC) activity in membrane preparations and did so primarily by altering the V max of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 30 publications
3
52
1
Order By: Relevance
“…Moreover, to preclude any effects of Cu 2ϩ or Zn 2ϩ on AC activity per se, after incubation of the G␣ s in the presence or absence of the metal cations, DTT (1 mM) was added. It has been shown that in the presence of DTT, Zn 2ϩ does not alter AC activity (22). Indeed, in our experiments also this treatment did not alter control activity of AC (Fig.…”
Section: Cusupporting
confidence: 55%
See 3 more Smart Citations
“…Moreover, to preclude any effects of Cu 2ϩ or Zn 2ϩ on AC activity per se, after incubation of the G␣ s in the presence or absence of the metal cations, DTT (1 mM) was added. It has been shown that in the presence of DTT, Zn 2ϩ does not alter AC activity (22). Indeed, in our experiments also this treatment did not alter control activity of AC (Fig.…”
Section: Cusupporting
confidence: 55%
“…Because cAMP plays a crucial role in the regulation of a number of cellular processes, one study has investigated the actions of Zn 2ϩ on ACs and shown that Zn 2ϩ inhibits the activity of type I, V, and VI ACs (22). The hormonal stimulation of cAMP was also attenuated by Zn 2ϩ (22).…”
Section: ؉mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that zinc deficiency lowers gestation and affects the nervous system, thus reducing appetite (Levenson, 2003). Many important enzymes and cytokines require zinc to function (Shankar and Prasad, 1998;Iskra and Majewski, 2000;McCall et al, 2000;Klein et al, 2002), and it is considered that zinc deficiency may adversely affect various vital functions and reduce metabolism and daily activity.…”
Section: Discussionmentioning
confidence: 99%